2021
DOI: 10.3390/pr9040618
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acids and Alkali as Additives on Hydrothermally Treating Sewage Sludge: Effect on Phosphorus Recovery, Yield, and Energy Value of Hydrochar

Abstract: The high moisture content present in sewage sludge hinders the use of sewage sludge in incineration or energy application. This limitation of moisture present in sewage sludge can be obviated by using the hydrothermal carbonization (HTC) process. In sewage sludge management, the HTC process requires less energy compared to other conventional thermo–chemical management processes. The HTC process produces energy-rich hydrochar products and simultaneously enables phosphorus recovery. This study investigates the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Hence, higher pH than 10 did not favor the adsorption process because addition of alkali reduces the activity of the adsorbent. The alkaline media may block the active sites and preclude them from the efficient adsorption [27]. The basicity results in repulsion of negatively charged ions, i.e., OH - and phosphate ion.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, higher pH than 10 did not favor the adsorption process because addition of alkali reduces the activity of the adsorbent. The alkaline media may block the active sites and preclude them from the efficient adsorption [27]. The basicity results in repulsion of negatively charged ions, i.e., OH - and phosphate ion.…”
Section: Resultsmentioning
confidence: 99%
“…These findings support the results of our study, where the decrease in initial pH from 8.32 to 2.25 led to a significant increase in TP concentration in liquor at all reaction temperatures, as shown in Table 3 . The extraction of P into HTC liquor at different conditions of initial pH was investigated by Shettigondahalli Ekanthalu et al (2021) , and their results confirmed the significant increase of P recovery in the liquor following the addition of inorganic acid ( Shettigondahalli Ekanthalu et al , 2021 ). Similar observations were reported by Shi et al (2021b) regarding the influence of acidic media on the release of P to HTC liquor ( Shi et al , 2021a ).…”
Section: Resultsmentioning
confidence: 71%
“…The pre-treated PW was well suited for subsequent anaerobic treatment [88]. Stutzenstein et al [92], use iron (III) nitrate as an alternative oxidant to treat PW from HTC of sewage sludge instead of oxygen [95]. After HTC, PW was collected with a COD of 70.00 g L −1 and TOC of 30.00 g L −1 .…”
Section: Wet Oxidationmentioning
confidence: 99%
“…This enables nutrient recovery. Many relevant scientific studies already exist on the topic, such as those by [4,44,95]. However, most studies focus on the recovery of nutrients from hydrochar.…”
Section: Nutrient Recoverymentioning
confidence: 99%